2020
DOI: 10.1101/2020.02.28.969477
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Controlling for Human Population Stratification in Rare Variant Association Studies

Abstract: 22 Population stratification is a strong confounding factor in human genetic association studies. In 23 analyses of rare variants, the main correction strategies based on principal components (PC) and linear 24 mixed models (LMM), may yield conflicting conclusions, due to both the specific type of structure 25 induced by rare variants and the particular statistical features of association tests. Studies evaluating 26 these approaches generally focused on specific situations with limited types of simulated stru… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Residual confounding refers to confounding that remains in an analysis, and can result from confounders that were unknown or unmeasured, confounders that were not adequately controlled for, and measurement error in the confounders that were adjusted (Kaufman et al, 1997). Rare variant analysis is particularly prone to residual confounding because individuals who share ultra‐rare variants are likely to have a recent common ancestor, and adjustment for principal components is insufficient to control for close relatedness (Bhatia et al, 2016; Bouaziz et al, 2021; Conomos et al, 2015; Persyn et al, 2018; Young, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Residual confounding refers to confounding that remains in an analysis, and can result from confounders that were unknown or unmeasured, confounders that were not adequately controlled for, and measurement error in the confounders that were adjusted (Kaufman et al, 1997). Rare variant analysis is particularly prone to residual confounding because individuals who share ultra‐rare variants are likely to have a recent common ancestor, and adjustment for principal components is insufficient to control for close relatedness (Bhatia et al, 2016; Bouaziz et al, 2021; Conomos et al, 2015; Persyn et al, 2018; Young, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Past research has indicated that rare variants can show different patterns of confounding than common variants 34 . To deal with this possibility, we applied a recently developed permutation method designed to control for type I error in genetic association tests of rare variants 23,37,38 . Specifically, we created an N × N distance matrix populated by scaled Euclidian distance of PC1-11 between each individual.…”
Section: Permutation To Further Control Effects Of Population Stratif...mentioning
confidence: 99%
“…Specifically, we created an N × N distance matrix populated by scaled Euclidian distance of PC1-11 between each individual. Then, we randomly exchanged genotypes of a given individual with one of their 100 nearest neighbors 23,38,48 . We created a total of 200 replicates of permuted genotypes and applied GREML with the same set of fixed and random covariates used in the main analysis.…”
Section: Permutation To Further Control Effects Of Population Stratif...mentioning
confidence: 99%
See 1 more Smart Citation
“…In fine-mapping, fine-scale population structure is a confounding variable of particular concern because rare variants tend to cluster geographically due to their recent origin (Mathieson and McVean, 2012). Adjusting for fine-scale population structure when fine-mapping rare variants is challenging, though recently proposed permutation approaches offer a potential way forward (Bouaziz et al, 2021). A.2 Sequence distances on partition sequence can be computed as follows.…”
Section: Performance Of Case-sequence Labelingmentioning
confidence: 99%